2017
DOI: 10.1016/j.brs.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral subthalamic nucleus deep brain stimulation on depression in Parkinson's disease

Abstract: Background Depression is common in Parkinson’s disease (PD) and adversely affects quality of life. Both unilateral and bilateral subthalamic (STN) deep brain stimulation (DBS) effectively treat the motor symptoms of PD, but questions remain regarding the impact of unilateral STN DBS on non-motor symptoms, such as depression. Methods We report changes in depression, as measured by the Hamilton Depression Rating Scale (HAMD-17), in 50 consecutive PD patients who underwent unilateral STN DBS. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
4
15
1
1
Order By: Relevance
“…[30] It is important to emphasize that the patients in our study underwent unilateral DBS. Our findings align with previously documented changes in ICD symptoms following unilateral DBS of both the STN and GPi [8] and further establish the potential for non-motor effects of unilateral DBS, previously shown to include changes in both mood [31] and cognition[33]. However, it remains unclear how bilateral DBS might have impacted these findings.…”
Section: Discussionsupporting
confidence: 90%
“…[30] It is important to emphasize that the patients in our study underwent unilateral DBS. Our findings align with previously documented changes in ICD symptoms following unilateral DBS of both the STN and GPi [8] and further establish the potential for non-motor effects of unilateral DBS, previously shown to include changes in both mood [31] and cognition[33]. However, it remains unclear how bilateral DBS might have impacted these findings.…”
Section: Discussionsupporting
confidence: 90%
“…This includes projections to hypothalamus and brainstem centers that coordinate the stress response [34], consistent with its activity correlating with increased cortisol release in stressed human subjects (see Table S2 in the Supplement of Reference [35]). BA25 also interconnects with the medial subthalamic nucleus [36], which, if playing a role similar to that in motor circuits, may provide pervasive inhibition relevant to symptoms of “mental paralysis,” a hypothesis supported by the antidepressant effects of subthalamic deep brain stimulation [37].…”
Section: The Pfc Circuitry In Primates Serving Top-down Controlmentioning
confidence: 99%
“…Even though bilateral STN-DBS is considered a relatively safe procedure, in the last years there has been a growing interest in unilateral and staged STN-DBS (i.e., implant of the two electrodes during two distinct surgical sittings separated over time), which involves lower surgical risk and less post-operative complications, such as cognitive dysfunctions ( 11 14 ). Alberts et al ( 13 ), for example, showed a decline in cognitive and motor functions when patients were examined under dual-task conditions only with bilateral but not with unilateral STN-DBS.…”
Section: Introductionmentioning
confidence: 99%